The mother, the nun, the writer, and the stranger: Female representation in Emilia Serrano’s América y sus mujeres - Salas Pino, Martha (2022)
Published in 1890, América y sus mujeres is one of the most important record books to (re)construct the woman’s history in the American continent. The product of a journey that lasted about fifteen years, Emilia Serrano recovers the names of the most outstanding women writers, journalists, heroines, religious women, among others, who inhabited America during the process of conquest until the end of the 19th century. Likewise, the writer classifies these women according to their western and religious values, proposing an ideal of woman that does not dialogue with the space of barbarism.